Limbal Stem Cell Dysfunction in Ichthyosis Follicularis, Alopecia, and Photophobia Syndrome. Issue 10 (October 2020) - Basilious, Alfred; Fung, Simon S. M.; Ali, Asim
Abstract : Purpose: To describe the presentation and management of limbal stem cell dysfunction in ichthyosis follicularis, alopecia, and photophobia (IFAP) syndrome. Methods: A retrospective case report. Results: A 6-day-old male infant was diagnosed with IFAP syndrome based on family history and a mutation detected in the MBTPS2 gene. Initial examination showed hyperkeratotic eyelids, madarosis, and lagophthalmos, but otherwise clear corneas. He developed bilateral central corneal epithelial defects spontaneously 6 months later, which were managed with aggressive lubrication, prophylactic antibiotics, and bilateral permanent lateral tarsorrhaphies at 7 months of age. During the procedure, the patient was noted to have bilateral limbal thickening, peripheral corneal pannus with underlying stromal scarring, and late fluorescein staining of the corneal surface. Anterior segment optical coherence tomography demonstrated a significantly abnormal and hyperreflective epithelial surface overlying a thinned corneal stroma, suggestive of limbal stem cell dysfunction. The corneal surface was maintained with lubrication and tarsorrhaphy and has remained stable since. Conclusions: The progressive conjunctivalization, spontaneous epithelial defects, and anterior segment optical coherence tomography features are highly suggestive of limbal stem cell dysfunction in IFAP syndrome. Optimizing the ocular surface is of importance in the management of children with this rare disease.